Digital dilemmas : exploring social media ethics in organizations (2020)
Social media platforms are at the core of the digital transformation of organizations. This chapter outlines the current study’s threefold purpose, which is to (1) categorize ethical dilemmas that can occur for professionals who run social media platforms for their organizations, (2) propose conceptual tools for reflecting on those dilemmas and (3) outline how social media ethics affects leadership in organizations. Social media enables individuals, groups and organizations to publish content without going through an editor, so it facilitates quick exchanges with a range of stakeholders. The current study is the first to map and categorize the ethical dilemmas that can occur in organizations that use social media. Input for the study comes from executive students at a European business school. The study’s overall aim is to provide a platform for systematic and reflective handling of ethical dilemmas for practitioners who are responsible for social media accounts at their organizations.